Factors Associated with Pregnant Women's Compliance with Fit-to-Fly Recommendations at El Tari Airport in 2024 - Indri Wahyuningsih Misnadin; Yendris Krisno Syamruth; Imelda Februati Ester Manurung; Pius Weraman; Christina Rony Nayoan (Journal of Epidemiology and Public Health, 2025)
Background: Fit-to-fly recommendations for pregnant women are regulated in Indonesia’s civil aviation guidelines. Noncompliance may pose health risks for both mother and fetus during air travel. This study aimed to identify factors associated with pregnant women’s compliance with fit-to-fly recommendations at El Tari Airport in 2024.Subjects and Method: A cross-sectional study was conducted from January to March 2024 at El Tari Airport, Kupang. A total of 130 pregnant passengers who applied for fit-to-fly letters at the BKK Class I Airport Health Post were selected using simple random sampling. The dependent variable was compliance with fit-to-fly recommendations. Independent variables included maternal age, gestational age, parity, education level, travel reasons, document completeness, exposure to information, family support, and maternal knowledge. Data were collected using a structured questionnaire and analyzed using univariate, bivariate, and multivariate methods with multiple logistic regression.Results: Gestational age (OR=6.79; 95%CI: 2.06–22.41; p=0.002), parity (OR=8.00; 95%CI: 2.61–22.54; p<0.001), education level (OR=5.49; 95%CI: 1.47–20.41; p=0.011), and maternal knowledge (OR=6.75; 95%CI: 2.13–21.34; p=0.001) were significantly associated with compliance. Other factors such as exposure to information, maternal age, document completeness, travel reasons, and family support showed no statistically significant association..Conclusion: Gestational age, parity, education level, and maternal knowledge were significant determinants of compliance with fit-to-fly recommendations among pregnant women. These findings highlight the importance of targeted health education and screening prior to air travel during pregnancy.